Penilaian Proses: Suatu Strategi untuk Meningkatkan Partisipasi Siswa Berbicara Bahasa Inggris - Delwita, Delwita (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2018)
Low students’ participation to speak during the learning process became a big problem in teaching English. Most students were anxious and reluctant to speak. They assumed that their participation to speak English in the classroom did not influence their report marks or their graduation. The researcher tried to overcome this problem by conducting a classroom action research for grade IX1 students of SMP 2 Kecamatan Lareh Sago Halaban, Kabupaten Lima Puluh Kota. In this case, the researcher applied a technique that is called assessment process while teacher monitored, supervised and gave marks toward students’participation to speak during the learning process. Based on the data analysis, it was found that the students’ participation to speak English increased 38% for 6 criteria of speaking activities: asking permission/request, responding command, asking and answering question, responding statement and expressing ide. And the students’ speaking ability could also be increased 26.9%. It can be concluded, the students’ participation to speak English could be improved through process assessment. And the factors, that could improve it, were giving score on every speaking activity done by students and teacher’s help to motivate them to speak English.